Industrial 4.0 Revolution: Can it Positively Step into a Sustainable Hospitality? - Elmohandes, Nirmeen; Csobán, Katalin (Applied Studies in Agribusiness and Commerce, 2022)
Technological advancements recently affected production, social and sustainable development. Few publications have addressed the industry 4.0 contribution to the sustainable hospitality industry. In this study, we review the ways and effectiveness of industry 4.0 in achieving sustainable development goals in the hospitality sector. Due to the modernity of the issue, resources used in this paper included articles from databases like SCOPUS, Sage, Elsevier, and google scholar using keywords such as big data analytics, simulation, Artificial intelligence, Industry 4.0 in hospitality, sustainable hotels, Industry 4.0 adaption in hospitality and smart hospitality system. This literature paper outline has five main sections—section one introduces industry 4.0. Section two is a literature review that includes Industry 4.0 connotation, sustainable development (SD), (SD) goals, challenges of (SD), and industry 4.0 solution for SD challenges. Industry 4.0 and sustainable hospitality. Section three is the methodology. The conclusion is the fourth section.JEL classification code: L83